2022
DOI: 10.1200/jco.22.00687
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, Diet, and Weight Management During Cancer Treatment: ASCO Guideline

Abstract: PURPOSE To provide guidance on exercise, diet, and weight management during active cancer treatment in adults. METHODS A systematic review of the literature identified systematic reviews and randomized controlled trials evaluating the impact of aerobic and resistance exercise, specific diets and foods, and intentional weight loss and avoidance of weight gain in adults during cancer treatment, on quality of life, treatment toxicity, and cancer control. PubMed and the Cochrane Library were searched from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
203
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(208 citation statements)
references
References 123 publications
4
203
0
1
Order By: Relevance
“…Based on other WHI research, guideline components may have changed in variable and opposing directions over the follow-up period. [33][34][35][36] The present study operationalized the 2012 guidelines to allow for direct comparisons with a limited body of literature that included minority cancer survivors 7,9,37 future studies should examine the new 2020 ACS guidelines 38 as well as the newly released guidelines for lifestyle management during cancer treatment, 39 not just in Black and Latina cohorts, but among all adults.…”
Section: Discussionmentioning
confidence: 99%
“…Based on other WHI research, guideline components may have changed in variable and opposing directions over the follow-up period. [33][34][35][36] The present study operationalized the 2012 guidelines to allow for direct comparisons with a limited body of literature that included minority cancer survivors 7,9,37 future studies should examine the new 2020 ACS guidelines 38 as well as the newly released guidelines for lifestyle management during cancer treatment, 39 not just in Black and Latina cohorts, but among all adults.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous benefits of exercise for patients with cancer have been documented, including mitigation of cancer- and treatment-related symptoms and improved health-related quality of life (HRQoL) [ 10 , 11 , 12 , 13 ]. Studies have also shown a positive effect of exercise on tumour control, with preclinical studies reporting that exercise suppressed tumour growth and rate of recurrence when delivered as a sole intervention [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise also enhanced the response to chemotherapy in the preclinical setting [ 21 ], and appeared to associate with improved disease-free survival in breast cancer patients undergoing adjuvant chemotherapy [ 22 ]. However, although ICIs comprise an important element of systemic therapy for cancer, the effect of combining ICIs with an exercise intervention is not well understood [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent survey evidence showed that while a high proportion of breast cancer patients reported at least one positive nutrition or physical activity behaviour after diagnosis or treatment, several treatment-related barriers (fatigue, stress, changes in appetite/taste disturbances, pain and discomfort) impeded the adoption of these health behaviours [ 28 ]. Furthermore, a recently published American College of Clinical Oncology Guideline paper emphasised the need for more research into diet and weight management strategies for people undergoing cancer treatments [ 29 ]. Thus, the aim of this qualitative study was to investigate the experiences and perceptions of overweight ER + BCPs regarding weight management (healthy dietary behaviours and physical activity) during and after primary treatment and ongoing hormone therapy.…”
Section: Introductionmentioning
confidence: 99%